Profilin1 E117G is a moderate risk factor for amyotrophic lateral sclerosis. Issue 5 (5th December 2013) - Fratta, Pietro; Charnock, James; Collins, Toby; Devoy, Anny; Howard, Robin; Malaspina, Andrea; Orrell, Richard; Sidle, Katie; Clarke, Jan; Shoai, Maryam; Lu, Ching-hua; Hardy, John; et al.
Abstract : Background: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are progressive neurodegenerative disorders that share significant clinical, pathological and genetic overlap and are considered to represent different ends of a common disease spectrum. Mutations in Profilin1 have recently been described as a rare cause of familial ALS. The PFN1 E117G missense variant has been described in familial and sporadic cases, and also found in controls, casting doubt on its pathogenicity. Interpretation of such variants represents a significant clinical-genetics challenge. Objective and results: Here, we combine a screen of a new cohort of 383 ALS patients with multiple-sequence datasets to refine estimates of the ALS and FTD risk associated with PFN1 E117G. Together, our cohorts add up to 5118 ALS and FTD cases and 13 089 controls. We estimate a frequency of E117G of 0.11% in controls and 0.25% in cases. Estimated odds after population stratification is 2.44 (95% CI 1.048 to ∞, Mantel-Haenszel test p=0.036). Conclusions: Our results show an association between E117G and ALS, with a moderate effect size.